Dubya Echoes Confirmation of Human-Induced Global Warming Theory and an Antioxidant Unravels - Shauna Haley (The Scientific World Journal)
U.S. President George W. Bush’s nod to scientific evidence for human industrialization’s major role in the onset of global climate change grabs both top story positions in Nature and Science this week.